The Right to the City and Laudato Si' Ethics: An Integrated Framework for Sustainable Urban Development - Nalle, Victor Imanuel W. (Journal of Contemporary Sociological Issues, 2025)
This article undertakes an analysis of the alignment between the right to the city and Laudato Si’, an encyclical issued by Pope Francis in 2015 to critique the global damages resulting from unchecked growth. The Laudato Si’ perspective offers a means to integrate ethical considerations into human rights law, providing a normative framework for sustainable development. Within these concepts, this article argues that incorporating the right to the city and Laudato Si’ may bridge the perspectives that are often understood as opposite, while demonstrating the need to develop a new understanding of sustainable cities. Additionally, by integrating these perspectives, it could increase awareness that cities serve as a prevalent home for multiple species, thereby necessitating a shift away from anthropocentrism. The interests of humans and ecology within the right to the city will contribute to improving the quality of life. To achieve this equilibrium, the development of the right to the city concept should provide a normative framework to: (1) curb the rapidification trend in urban development conflicting with the naturally slow pace of biological evolution, (2) eliminate the privatization of spaces restricting citizens’ access to basic needs, and (3) reinforce community participation, especially among the poor and vulnerable, in urban planning. Undoubtedly, the realization of such a normative framework faces challenges within a developmentalist state oriented towards high economic growth. Keywords: right to the city; Laudato Si’; sustainable development